Biphasic P wave in inferior leads and the development of atrial fibrillation. Issue 6 (12th August 2015) - Hayashi, Hideki; Horie, Minoru
Abstract: Background: Anisotropic and slow conduction in the atrium underlie the development of atrial fibrillation (AF). This study aimed to investigate the P wave characteristics associated with the development of AF in patients with a biphasic P wave in the inferior leads. Methods: Digital analysis of retrospectively recorded 12‐lead electrocardiograms was performed to select patients with a biphasic P wave (positive/negative) in lead II from a database of 114, 334 patients. Characteristics of the P wave in the inferior leads associated with incidence of AF were determined. Receiver operating characteristic curves dichotomized P wave variables were measured in each lead. Results: A total of 141 patients (77 men; mean age, 64±19 years) were enrolled in this study. Twenty‐nine (20.6%) patients developed AF (AF group) vs. 112 (79.6%) who did not (non‐AF group) during a follow‐up period of 50±62 months. The amplitude of the initial P wave portion in lead II was significantly larger in the AF group when compared with the non‐AF group (77.3±77.0 µV vs. 51.0±30.1 µV, p =0.003), while the amplitude of the terminal P wave portion in lead III was significantly decreased in the AF group when compared with the non‐AF group (−70.6±41.3 µV vs. −89.1±38.1 µV, p =0.024). The duration of the initial P wave portion in lead III was significantly longer in the AF group when compared with the non‐AF group (52.7±34.6 ms vs. 35.8±30.4 ms, p =0.011). Multivariate Cox proportional‐hazards analysis confirmed that the increased duration of the initial P wave portion in lead III (≥71 ms) was independently associated with AF development (hazard ratio 2.90, 95% confidence interval 1.16–7.11, p =0.02). Conclusion: The analyses of the biphasic P wave in the inferior leads suggest that the development of AF could be attributed to increased atrial slow conduction.